Pre- and post-dilatation in transcatheter aortic valve implantation with self-expanding valves: a systematic review and meta-analysis - Bing Wei Thaddeus Soh; Ailís Pollock; Dominic Butler; Angela McInerney; John William McEvoy; Darren Mylotte (Frontiers in Cardiovascular Medicine, 2026)
Introduction Pre-dilatation balloon aortic valvuloplasty (PRE-BAV) and post-dilatation (POST-DIL) are commonly used during transcatheter aortic valve implantation with self-expanding valves (SEV-TAVI) to facilitate device delivery and optimize valve expansion, but both may increase procedural complications. Methods We conducted a systematic review and meta-analysis to evaluate outcomes associated with PRE-BAV and POST-DIL compared with direct implantation (DIRECT) and valves left as deployed (AS-DEPLOYED), respectively. Eleven studies (nine observational, two randomised; 24,143 patients) were included for PRE-BAV and five observational studies (7,526 patients) for POST-DIL. Key outcomes included mortality, stroke, permanent pacemaker implantation, and moderate or greater paravalvular leak (PVL2+). Random-effects meta-analyses with Hartung–Knapp–Sidik–Jonkman adjustment were used to estimate pooled odds ratios (ORs) with 95% confidence intervals (CIs). Results Compared with DIRECT, PRE-BAV was not associated with differences in mortality, stroke, pacemaker implantation, or PVL2+, but randomised data showed a reduced need for POST-DIL (OR 0.43; 95% CI 0.24–0.74). Compared with AS-DEPLOYED, observational series suggested that POST-DIL was linked to higher 30-day mortality (OR 1.39; 95% CI 1.18–1.63), increased PVL2+ (OR 3.76; 95% CI 2.13–6.63), and more frequent surgical conversion (OR 1.22; 95% CI 1.06–1.41), with no differences in stroke or pacemaker implantation. Discussion PRE-BAV was not associated with increased adverse outcomes and may reduce the need for post-dilatation, whereas the adverse outcomes observed with POST-DIL in observational studies are most likely explained by confounding by indication rather than a causal effect. Further adequately powered randomised trials are needed to define the optimal balloon dilatation strategy in SEV-TAVI. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/view/CRD42024610604 .